A Case of Asynchronous Media Change in the 1950s: How US-American TV Series Came to Early West German Television (Global Media Journal - German Edition, 2016)
The influence of radio and cinema on the first television program designs in West Germany, and other nations, can be explained by a theory which has recently been put forward by communication scholar Gabriele Balbi. According to Balbi, in a first step new media imitate old media in manifold ways before they develop characteristics of their own and become a truly new medium. However, the 'producers' of early West German national television were not only looking to radio or cinema for clues on how to design the program of Deutsches Fernsehen (DFS), West Germany's first and only national television channel from 1954 to 1961/63. DFS' executives and executive employees were also looking to other nations, particularly to those – like the United States – that were years ahead in television's evolution. Especially the implementation of the entertainment series in West German television is strongly rooted in visits to the United States and newly gathered information and impressions. To exemplify this argument, I delve into examples which demonstrate that West German television executives and executive employees were either creating television series on the basis of US-American television series or were broadcasting the latter after synchronization. In this context, major findings of diffusion research constitute a useful addition to current theories on media change.
Keywords: media change; television history; TV series; USA; West Germany; diffusion theory